2007
DOI: 10.1158/1055-9965.epi-07-0153
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of TP53 Mutations in Relation to Arg72Pro Genotypes in Non–Small Cell Lung Cancer

Abstract: Mutations in the TP53 gene are important events during human lung carcinogenesis. The TP53 gene harbors several polymorphisms, and functional studies have shown that the Arg72Pro polymorphism alters both wild-type and mutant p53 protein activity. Thus, we hypothesized that certain Arg72Pro genotypes may influence the frequency and pattern of somatic mutations in TP53. We therefore examined the status of the Arg72Pro polymorphism and TP53 mutations in 260 non -small-cell lung cancer cases. Here we report a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…7 Finally, Pro72 allele carriers show significantly lower frequency of TP53 mutations in specific types of human non-hematologic tumors. 13 Here, we demonstrated that the TP53 Pro/Pro genotype was associated with higher risk of leukemia and favorable outcome in AML patients treated with conventional therapy, particularly those assigned to the intermediate cytogenetic risk group. Therefore, it seems that the TP53 Arg72Pro polymorphism may have different tissue-and context-specific functions, and the prognostic importance of each allele may depend on the type of cancer and on the particular treatment.…”
Section: Tp53 Arg72promentioning
confidence: 72%
“…7 Finally, Pro72 allele carriers show significantly lower frequency of TP53 mutations in specific types of human non-hematologic tumors. 13 Here, we demonstrated that the TP53 Pro/Pro genotype was associated with higher risk of leukemia and favorable outcome in AML patients treated with conventional therapy, particularly those assigned to the intermediate cytogenetic risk group. Therefore, it seems that the TP53 Arg72Pro polymorphism may have different tissue-and context-specific functions, and the prognostic importance of each allele may depend on the type of cancer and on the particular treatment.…”
Section: Tp53 Arg72promentioning
confidence: 72%
“…Interassay variation was generally <20%. Analysis of TP53 mutations in lung tumor tissues was performed as previously described 20…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, p53 degradation is prevented by inhibition of the Mdm2 regulator p14 ARF, or by deubquitination by HAUSP [33][34][35][36][37]. The Hdm2 gene is amplified in approximately 10% of solid tumors [36] and mutations in the HAUSP and Hdm2 genes are frequently associated with non-small-cell lung cancer and colorectal cancer [38][39][40].…”
Section: Function Of the Ups In Carcinogenesismentioning
confidence: 99%